Mapping the dualism of nature/society and nature/culture in environmental sciences in view of the anthropocene - Hočevar, Marjan (Družboslovne razprave, 2023)
This study uses the qualitative method of chronological and analytical literature review complemented with the visualisation (VOSviewer) of documents extracted from the Scopus database to consider a fundamental dualism of “culture and nature” and/or “society and nature” in the context of interdisciplinary approaches to environmental studies. The visualisations reveal clusters that manifest themselves differently when the nature/culture and nature/society pairs are compared. The term Anthropocene, adopted as a concept, is highlighted as a model to test the flattening of the dualism in question. The concept of the Anthropocene can serve as a prototypical link in research on environmental interdisciplinarity.
Keywords: Antropocen; antropocentrizem; bibliometrija; družba; Družbeni vidik; Kultura; Narava; narava - družba; narava - kultura; okoljevarstvo